Isolation of a transcription factor DREB1A gene from Phaseolus vulgaris and computational insights into its characterization: protein modeling, docking and mutagenesis - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS INC, 2017)
A transcription factor DREB1A (dehydration-responsive element-binding 1A) gene was amplified and sequenced from the common bean (Phaseolus vulgaris). PvDREB1A had a 777 base pairs (bp) open reading frame encoding a protein of 225 residues. The protein sequence contained a conserved DNA-binding AP2 domain of about 60 residues and a nuclear localization signal (NLS) at N-terminus site. PvDREB1A demonstrated high homology with other DREB1 members only in AP2 domain and NLS site. The phylogenetic distribution of different DREB members showed three main groups as DREB1-3 and PvDREB1A was a member of DREB1 group. Homology modeling and secondary structure analyses revealed that PvDREB1A AP2 domain was packed into the three-stranded antiparallel beta sheets (beta 1-3) and an alpha helix (alpha 1) almost parallel to these beta sheets. Moreover, DNA-binding AP2 domain of PvDREB1A and GCC-box containing double helix DNA were docked. The docking analysis showed that PvDREB1A AP2 domain could bind to the major groove of the DNA by three-stranded antiparallel beta sheets, with residues Gly86 or Thr87 in beta 1-sheet and Arg63 or Arg64 in beta 3-sheet. The docked complex also indicated that AP2 domain has a preferential for the binding of GCC stretches in the double helix DNA. A total of 36 reliably estimated hot spots residues were identified with high mutability grade but none of these residues was essential for the protein function since they are located at outside the DNA-binding AP2 domain of PvDREB1A.
Keywords: transcription factor; DREB; AP2 domain; homology modeling; docking; GENOME-WIDE ANALYSIS; DNA-BINDING DOMAIN; ORYZA-SATIVA; FUNCTIONAL-ANALYSIS; HIGH-SALT; STRESS TOLERANCE; LOW-TEMPERATURE; ABSCISIC-ACID; AP2 DOMAIN; DROUGHT